Grammaire castillane de Cristóbal de Villalón - de Villalón, Cristóbal (Sources, 2021)
The Gramática castellana de Villalón was published in 1558 by Cristóbal de Villalón. The present book offers a translation into French of this grammar, with a critical apparatus of notes that allows a better understanding of the linguistic and cultural context of the 16th century, which constitutes the frame of reference of this grammar.